#TITLE_ALTERNATIVE# - Hidayat (NIM 25394007), Antun
Abstrak : Removing NH3 and H2S in advanced wastewater treatment has been carrying out by physic-chemical operation air stripping packed column. The basic phenomena are differences between the solute concentration in liquid phases and concentration in equilibrium that the driving forces causing the gas transfer. Overall mass transfer rate constant (KLa) determined experimentally at a packed column and packed with Rashig rings. Experiments yields were compared with rate constants predicted by correlation model of Onda. The efficiency of NH3 removal would higher in pH base conditions, meanwhile H2S removal would higher in pH acid conditions. The air-water ratio had significant values in NH3 and H2S removal and it was showing optimum efficiency point on ratio 200:1 that indicating lower than computed theory from mass-balance. Improvement of NH3 and H2S removal in packed column from column have no packed were evidenced that packed area gave longer contact time (t) between air to water beside of water bubble area (a). Over-all Mass Transfer Rate Constant - showing of gradient of reaction rate velocity of stripping - obtained from basic design expression Z = HTU x NTU. The values KLa would higher with high of hydraulic loading, longer time contact process and higher stripping factor (S) that showed by air-water ratio. The deviation of KLa experiments to prediction with Onda models caused by differences of experiments air-water ratio were lower than model range.